Novas funcionalizações na fibra da casca de coco verde visando um suporte para imobilização de enzimas - Morais, Jessica Silva de Almeida (2020)
Several materials have been investigated as potential supports for immobilizing enzymes. Among them, the fiber of green coconut shell stands out because it is very affordable, and rich in cellulose and lignin. Thus, the objective of this work was to develop a new obtention method for supports to immobilize enzymes, from the fiber of the green coconut shell. Initially, the most efficient hydrogen peroxide concentration for fiber pretreatment was evaluated. The condition of 4.5% hydrogen peroxide at pH 11.5 was selected. After this stage, two functionalization methods were evaluated. In the functionalization by oxidation with sodium periodate the effect of time and fiber:reagent ratio were studied and 198 µmol of aldehyde 1g fiber groups were obtained. For the functionalization with tosyl groups, variations in time, reagent concentration, and in the base present in the medium were tested. Based on environmental impact data provided by the SimaPro Software and by Scanning Electron Microscopy using Dispersive Energy Spectroscopy, it was possible to verify that triethylamine was the base that caused the least negative environmental impact and greater capacity to incorporate tosil groups in the fiber. Crude, pre-treated and functionalized fibers were evaluated for stability when subjected to different reaction media (phosphate buffer pH 5, 7 and 9, ethanol, ethanol together with oil (1: 1), and only oil), at temperatures 40 and 50 ° C, under stirring for 7 days. FTIR, TGA and colorimetry analyzes showed preservation of the lignocellulosic structure and removal of extracts and waxes. Immobilizations using Candida antarctica lipase B (CALB) in the functionalized fibers after pretreatment (FF) and after washing (FLF) occurred under conditions of pH 7 and pH 10, 2 and 24h and temperature of 25 °C. It was possible to immobilize CALB on both tested supports. The greater activity was presented by FF at pH 7 for 24h, with a value of 1039 U / Kg. It was possible to treat the fibers using alkaline peroxide and functionalize them with sodium periodate to later perform the immobilizations. Tests with p-toluenesulfonyl chloride have also shown potential, however future studies will be needed to optimize the condition of this reaction.